Services offshoring and wages: evidence from micro data - Geishecker, Ingo; Görg, Holger (Nottingham, 2008)
"We show that services offshoring affects the real wage of low and medium skilled individuals negatively. By contrast, skilled workers benefit in terms of higher real wages. Hence, offshoring has contributed to a widening of the wage gap between skilled and less skilled workers."